Sistem Informasi Pembelian dan Penjualan Obat di Apotek Berbasis Website - R Fenny Syafariani; Dicky Ginanjar; Euis Neni Hayati (Universitas Negeri Padang, 2021)
Pharmacy is a company that engages in the field of drug supply. In general, the system that runs at the pharmacy is still performed manually, starting from recording transactions, stocks checking, drug stocks data processing and recording, transaction calculation process, and the process of making reports. The fact that these processes were done manually makes the process to be not optimal. The purpose of this research is to determine the problems faced by the current system and propose a system design. Then, test the system and finally implement the information system on drug purchases and sales at the pharmacy. The method used a structured development method as well as the Waterfall method as a software development method. The results of this study present a drug purchase information system at a pharmacy to help facilitate the sale and purchase of goods from the pharmacy to the customer and supplier. With a drug purchase information system, pharmacies can minimize transactions that are done manually so that they can be upgraded to be computerized. By implementing the information system on drug purchases and sales at the pharmacy, it is expected to be able to overcome the problems faced by the current system at the pharmacy in order to be able to maximize the transaction process and to increase revenue from the pharmacy